2018
DOI: 10.1021/jacs.8b03847
|View full text |Cite
|
Sign up to set email alerts
|

Nanocarbon-Based Glycoconjugates as Multivalent Inhibitors of Ebola Virus Infection

Abstract: SWCNTs, MWCNTs, and SWCNHs have been employed as virus-mimicking nanocarbon platforms for the multivalent presentation of carbohydrates in an artificial Ebola virus infection model assay. These carbon nanoforms have been chemically modified by the covalent attachment of glycodendrons and glycofullerenes using the CuAAC "click chemistry" approach. This modification dramatically increases the water solubility of these structurally different nanocarbons. Their efficiency in blocking DC-SIGN-mediated viral infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 100 publications
0
50
0
1
Order By: Relevance
“…Graphene can disrupt the C-terminal domain interface of VP40 hexamers being crucial in forming the Ebola viral matrix, suggesting that graphene or similar NPs-based solutions used as a disinfectant could notably reduce the spread of the disease and prevent an Ebola epidemic (Gc et al 2017). Rodriguez-Perez et al (2018) found that MWCNTs functionalized with glycofullerenes can be considered as potent inhibitors of Ebola infection. In two mRNA vaccines based on the EBOV envelope glycoprotein, differing by the nature of signal peptide for improved glycoprotein posttranslational translocation, the mRNAs were formulated with LNPs to facilitate delivery.…”
Section: Ebola and Marburg Virusmentioning
confidence: 99%
“…Graphene can disrupt the C-terminal domain interface of VP40 hexamers being crucial in forming the Ebola viral matrix, suggesting that graphene or similar NPs-based solutions used as a disinfectant could notably reduce the spread of the disease and prevent an Ebola epidemic (Gc et al 2017). Rodriguez-Perez et al (2018) found that MWCNTs functionalized with glycofullerenes can be considered as potent inhibitors of Ebola infection. In two mRNA vaccines based on the EBOV envelope glycoprotein, differing by the nature of signal peptide for improved glycoprotein posttranslational translocation, the mRNAs were formulated with LNPs to facilitate delivery.…”
Section: Ebola and Marburg Virusmentioning
confidence: 99%
“…An increasing number of antiviral nanomaterials have been developed by interfering with the interaction between virus and its associated cell receptor to achieve broad-spectrum efficacy. 14,15 Heparan sulfate proteoglycans (HSPGs) are reported to act as receptors of many viruses, such as dengue virus, human cytomegalovirus (HCMV), human immunodeciency virus (HIV), respiratory syncytial virus (RSV), herpes simplex virus (HSV), loviruses and human papillomavirus (HPV). 16 Heparan sulfates (HS), an important constituent of HSPG, are structurally similar to heparin.…”
Section: Introductionmentioning
confidence: 99%
“…[23] With this background, inhibition of DC-SIGN-mediated attachment of viral particles to innate immune cells represents a promising strategy for the development of antiviral drugs. [24][25][26] In the past, this strategy has been investigated for the treatment of HIV, [20] ebola, [27] zika, [28] and dengue infections. [28] In view of the recent emergence of the SARS-CoV-2 pandemic, DC-SIGN-targeted antivirals could represent a promising host-directed treatment option for COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism leads to an increase in apparent binding affinity of protein-carbohydrate interactions of up to a factor of 10 6 . [32,33] In this context, functionalized polymeric supports, [34] peptides, [35] dendrimers, [36] nanoparticles, [37] fullerenes, [28] carbon nanotubes, [27] and thiacalixarenes [38] have been studied. However, a severe drawback of some of these nonbiodegradable multivalent scaffolds is their potential accumulation and associated toxicity, especially when prolonged pulmonary applications are considered.…”
Section: Introductionmentioning
confidence: 99%